Assessment of the Glycotronic C blood glucose meter. Issue 9 (September 1991) - Forrest, A R; Pitt, E J
Abstract : The performance of the Glycotronic C blood glucose meter, a pocket sized glucose strip meter, was assessed on the ward and in the laboratory. Theoretically there is a relation between blood glucose concentration, plasma glucose concentration and haematocrit when glucose is measured using conventional methods. The Glycotronic C meter would yield results about 20% greater than those of a conventional instrument when used to measure plasma glucose and about 15% less than a conventional instrument when used to measure the blood glucose concentration of a neonate. The Glycotronic C is easy to use and gives an acceptable performance for near patient use; it compares well with its current British competitors.